Study of output factors of electron beam based on the simple model - Sohaimi, Norhanna (2004)
The output factors for clinical electron beams have been shown to be dependant on beam energy, field size and collimator design. The purpose of this study was to investigate the application of the equation of the output factors for a rectangular field size, which developed from Gaussian scatter model for electron beams used in Radiotherapy Department, Universiti Sains Malaysia Hospital. The output factors were measured for 5 MeV and 10 MeV electron beams for various applicators and square or rectangular insert combinations used in clinical services. The field sizes ranged from 3 em x 3 em to 25 em x 25 em at source to surface distance of 1 00 em. The parallel plate ionization chamber was used to collect the charge and was placed at dmax inside the solid water material for each electron beam energies. Calculated output factors for the fields studied agreed with the measured output factors within ±2o/o. This demonstrated that for this Linear Accelerator {MXE; LINAC MEVATRON), the output factors calculated in homogenous solid water phantom could be predicted accurately using theoretical formula.